The association of enteric neuropathy with gut phenotypes in acute and progressive models of Parkinson’s disease - Rachel M. McQuade (Nature Portfolio, 2021)
Abstract Parkinson’s disease (PD) is associated with neuronal damage in the brain and gut. This work compares changes in the enteric nervous system (ENS) of commonly used mouse models of PD that exhibit central neuropathy and a gut phenotype. Enteric neuropathy was assessed in five mouse models: peripheral injection of MPTP; intracerebral injection of 6-OHDA; oral rotenone; and mice transgenic for A53T variant human α-synuclein with and without rotenone. Changes in the ENS of the colon were quantified using pan-neuronal marker, Hu, and neuronal nitric oxide synthase (nNOS) and were correlated with GI function. MPTP had no effect on the number of Hu+ neurons but was associated with an increase in Hu+ nuclear translocation (P < 0.04). 6-OHDA lesioned mice had significantly fewer Hu+ neurons/ganglion (P < 0.02) and a reduced proportion of nNOS+ neurons in colon (P < 0.001). A53T mice had significantly fewer Hu+ neurons/area (P < 0.001) and exhibited larger soma size (P < 0.03). Treatment with rotenone reduced the number of Hu+ cells/mm2 in WT mice (P < 0.006) and increased the proportion of Hu+ translocated cells in both WT (P < 0.02) and A53T mice (P < 0.04). All PD models exhibited a degree of enteric neuropathy, the extent and type of damage to the ENS, however, was dependent on the model.